Geotechnical assessment of the morrenic aggregate and its impact on the compressive strength and durability of concrete in Sapallanga - Huancayo - Junín Region - Andía Arias, Janet Yéssica (2018)
Morrenic aggregates from the quarry of Sapallanga – Chaclas River, have been evaluated geotechnically through laboratory tests to obtain their physical properties. Likewise, other tests of aggregate quality and mix design by resistance and durability have been performed. The evaluation that was carried out allowed classifying the samples of morrenic aggregates into three groups: low weathering, medium weathering, and high weathering. After obtaining the results of the laboratory tests of morrenic aggregates, it was found that they surpass 100% of the design resistance at 28 days. Additionally, it was verified that morrenic aggregates of the Sapallanga - Chaclas Riveer quarry meet the quality requirements of aggregates established in the Peruvian Technical Standard 400.037.